Assessment of Regional Perfusion and Organ Function: Less and Non-invasive Techniques - Huber, Wolfgang; Zanner, Robert; Schneider, Gerhard; Schmid, Roland; Lahmer, Tobias (Frontiers in Medicine, 2019)
Sufficient organ perfusion essentially depends on preserved macro- and micro-circulation. The last two decades brought substantial progress in the development of less and non-invasive monitoring of macro-haemodynamics. However, several recent studies suggest a high prevalence of incoherence of macro- and micro-circulation. Therefore, this review reports on interactions of macro- and micro-circulation as well as on regional and micro-circulation. Regarding global micro-circulation the last two decades brought advances in a more systematic approach of clinical examination including capillary refill time, a graded assessment of mottling of the skin and accurate measurement of body surface temperatures. As a kind of link between macro- and microcirculation, a number of biochemical markers can easily be obtained. Among those are central-venous oxygen saturation (ScvO2), plasma lactate and the difference between central-venous and arterial CO2 (cv-a-pCO2-gap). These inexpensive markers have become part of clinical routine and guideline recommendations. While their potential to replace parameters of macro-circulation such as cardiac output (CO) is limited, they facilitate the interpretation of the adequacy of CO and other macro-circulatory markers. Furthermore, they give additional hints on micro-circulatory impairment. In addition, a number of more sophisticated technical approaches to quantify and visualize micro-circulation including video-microscopy, laser flowmetry, near-infrared spectroscopy (NIRS) and partial oxygen pressure measurement have been introduced within the last 20 years. These technologies have been extensively used for scientific purposes. Moreover, they have been successfully used for educational purposes and to visualize micro-circulatory disturbances during sepsis and other causes of shock. Despite several studies demonstrating the association of these techniques and parameters with outcome, their practical use still is limited. However, future improvements in automated structured and “online” diagnosis will help to make these technologies more applicable in clinical routine. This approach is promising with regard several studies which demonstrated the potential to guide therapy in different types of shock. Finally several organs have specific patterns of circulation related to their special anatomy (liver) or their auto-regulatory capacities (brain, kidney). Therefore this review also discusses specific issues of monitoring liver, brain and kidney circulation and function.